Protective role of CoQ10 in reducing the side effects resulting from the use of Tramadol on some immunological variables in the endemic female rabbits - Hanan Shihab Ahmad Hussain; Zaid M.Mubark AL-Mahdawi; Muneef Saab Ahmed Aljanabi (Tikrit Journal of Pure Science, 2023)
The aim of study to determine out the role of CoQ10 in reducing the side effects from the use of Tramadol on the level of Interlukin IL-6, IL-10 and PGF2α the study included 30 endemic female rabbits, where each group included  5 animals. The results showed increase with a highly significant with (P≤0.01) in the concentration of IL-10 in sera of treated group with tramadol (initial dose) and group treated tramadol (double dose) group treated tramadol (initial dose + CoQ10) and group treated  with tramadol (double dose + CoQ10) compare with control.